The Development of Audio Visual Learning Media in Improving Children’s Religious and Moral Values - Lubis, Latifahanum; Khadijah, Khadijah; Hasibuan, Humaidah Br. (Universitas Pahlawan Tuanku Tambusai, 2022)
Morality and religion are the main fortresses for the formation of children's character in responding to the flow of globalization in the digital era. The form of concrete efforts is carried out through a quality learning process for children. This study aims to develop audio-visual learning media in improving the religious and moral values of early childhood. The author uses the type of research R&D (Research and Development). The use of this research method is intended to produce new products in learning and to test the effectiveness of these products. In this context, the product that will be produced is in the form of media in the form of the film